A Predictive Model of the Effects of Depression, Anxiety, Stress, 6-Minute-Walk Distance, and Social Support on Health-Related Quality of Life in an Adult Pulmonary Hypertension Population. Issue 1 (January 2015) - Tartavoulle, Todd Michael
Abstract : Purpose: Pulmonary hypertension (PH) is a life-limiting chronic disease that presents as an elevated blood pressure in the pulmonary artery. The uncertainty of the disease has a profound effect on relationships, cognitive ability, spirituality, emotions, and exercise ability and can negatively impact health-related quality of life (HRQOL). The purposes of this cross-sectional, predictive, correlational study were ( a ) to identify relationships among the psychological factors (depression, anxiety, stress), physiological factor (6-Minute Walk Test), situational factor (social support), and HRQOL and ( b ) to test a structural equation model in which depression, anxiety, stress, social support, and 6-minute walk distance predict HRQOL in adults with PH. Sample and Setting: A convenience sample of 166 adults between the ages of 21 and 80 years were recruited from the Pulmonary Hypertension Association's 10th International Pulmonary Hypertension Conference and Scientific Sessions in Orlando, Florida, and a PH clinic in southeast Louisiana. Each subject completed 2 questionnaires: the 21-item Depression Anxiety Stress Scale and the Dartmouth Cooperative Functional Assessment Charts. Results: The findings indicated a relationship between depression, stress, anxiety, 6-Minute Walk Test, social support, and HRQOL. The data collected from the adult PH population fit the proposed predictive model for adults with PH HRQOL. However, the researcher was unable to determine the best predictor of HRQOL in adults with PH. Conclusions: The findings indicate depression, anxiety, stress, 6-minute walk distance, and social support play important roles in HRQOL among patients with PH. Advanced practice nursing strategies to increase HRQOL include counseling, psychiatric referrals, psychotherapy, guided imagery, leading support groups, and low-grade resistance training.